Improving the Quality of Green Coffee Beans through an IoT-Based Moisture Content Measuring Device for Coffee Farmers in Datar Lebar Village, Semendo Darat Ulu, Muara Enim. - Handayani, Marta Tika; Tompunu, Alan; Masnila, Nelly (JAKADIMAS (Jurnal Karya Pengabdian Masyarakat), 2026)
The quality of green coffee beans is highly influenced by post-harvest moisture content. Coffee farmers in Datar Lebar Village face challenges due to the absence of accurate moisture measuring devices, resulting in traditional drying methods based on experience. This community service program aimed to improve green bean quality through the implementation of an Internet of Things (IoT)-based moisture meter. A participatory approach was applied, including problem identification, device development, implementation, training, and evaluation. The results showed a decrease in average moisture content from 13.8% to 11.2% and a reduction in variation from ±1.2 to ±0.5. Approximately 85% of farmers were able to operate the device independently. The technology implementation improved product uniformity and economic value. This program represents an initial step toward smart agriculture at the village level.